A família cristã católica: o movimento noelista na Paraíba (1931-1945) - Gomes, Jorilene Barros da Silva (2015)
This work search to discuss and question from texts produced by the Paraíba Noelista Center that are in the newspaper A Imprensa, specifically the section titled “Women's Culture” and the group's meeting minutes that are located in the Archdiocese of Paraíba the model ideal of Catholic Christian family, between the years 1931-1945, with perspective to understanding the social formation, ideological and religious family in Paraíba in the first half of the twentieth century. The Noelista Center in Paraíba is a movement of the branch "Le Noel" that originated in France in the late nineteenth century, by Father Paul Bailly and founder of the movement and also Father Claude Allez. The movement was created in the context of reorganization of the Catholic Church (the process of Romanization) that had as main objective to fight the deviant aspects of modernity. Noel was brought to Brazil in 1914 for the city of Recife and spread through several states of Brazil in the following years, with the core state of Pernambuco and vice core the state of Rio de Janeiro and settled in Paraiba year 1931. Among the movement of the main features in Brazil, stand out: the assistantiality, catechesis, charity and the formation of individual and collective faith. This paper focuses specifically on the analysis of texts produced by noelistas in the Paraiba, because these texts possible to understand debates about family life that report the main dilemmas of the period as virginity, marriage, work, motherhood, etc. Therefore, it is done in this research the intersection between the influences of what would be considered modern for the time and conservative family values postulated by the Catholic Church to understand how this "ideal type" of family adapted to the new models and winds of modernity. So when do these two texts is a privilege, it is possible to dive through the poems that has a character novelists tangles of sensations and dilemmas that relate to the concepts of affection, sociability and religion among the families of the twentieth century.